Al-Hawalah as a Concept in Sharia Banking - Sugih Nugraha; Hudallah (Penerbit Hellow Pustaka, 2025)
Al Hawalah, as a concept in sharia banking, has a rich historical background in the development of Islamic economics. A debt transfer method regulated by sharia law, Al Hawalah has been an integral part of the Islamic financial system since the beginning of Islamic civilization. This concept is rooted in the practice of Rasulullah SAW and his friends in handling financial transactions. Al Hawalah emphasizes the values of mutual trust, justice and compliance with sharia provisions in maintaining the integrity of Islamic financial transactions. By continuing to develop, Al Hawalah has become a relevant instrument in supporting the principles of modern sharia banking.